(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Submerged arc welding (SAW) is a fusion type welding and it is considered as one of the most important welding types due to its inherent capabilities of high welding speed, high deposition rate, welding large thickness plates owing to its deep penetration characteristic and many other advantages. In this study, the goal was to investigate the effect of welding parameters, namely (welding current and welding speed) as well as the joint design on the mechanical properties (yield stress, bending force on the face of the weldment and hardness of the weld metal. Experiments were conducted employing Design of Experiment (DOE) software and Response Surface Methodology (RSM) technique. The experiments were performed by welding (26) pieces of ASME SA-516 Gr. 70 steel plate with dimensions of (300 mm × 150 mm × 10 mm) to produce (13) specimens depending upon the design matrix developed via the DOE. Results manifested that the optimum process parameters for maximum yield stress, maximum bending force and minimum hardness were (202.659 MPa, 21.662 KN and 139.232 HV), respectively at (425 amps) welding current and (35 cm/min) welding speed, where the arc voltage was held constant at (37 volts). Finally, it was found that the predicted and experimental results of yield stress, bending force and hardness agree very well according to the ultimate error (1.5%, 1.3%, and 3.4 %), respectively.